A Novel Approach for Security in Digital Image Processing Using Water Marking: Analysis - Kaur, Prabhpreet; Kanotra, Sonali (International Journal of Computer Sciences and Engineering, 2025)
In this era of digital security, protection and illegal redistribution of digital media has become a major issue. The digital watermarking has been utilized to shield digital data from illicit redistribution and changes. In digital water denoting the image has been upgraded by installing commotion tolerant flag into transporter flag. Encryption procedures used to encode critical information has been inclined to assaults or attacks. Assist examination in encryption yields image encryption instrument as contrasting option to content encryption. The investigation of different system of digital watermarking as image encryption has been done in this paper to examine techniques which are better and can be used in future for enhancement; likewise the commitment of watermarking methods for security purposes has been broke down. The proposed literature provides comparative studies of techniques used in watermarking along with attributes considered including PSNR and MSE for enhancement.